2019
DOI: 10.35799/jbl.9.1.2019.23421
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Antara Riwayat Pemberian Imunisasi dan Penyakit Infeksi dengan Status Gizi pada Anak Usia 24-59 Bulan di Kecamatan Ratahan Kabupaten Minahasa Tenggara. (Relationship Between History of Immunization and Infectious Disease with Nutritional Status in Children aged 24-59 Months in Ratahan Subdistrict, Southeast Minahasa Regency)

Abstract: Hubungan Antara Riwayat Pemberian Imunisasi dan Penyakit Infeksi dengan Status Gizi pada Anak Usia 24-59 Bulan di Kecamatan Ratahan Kabupaten Minahasa Tenggara.(Relationship Between History of Immunization and Infectious Disease with Nutritional Status in Children aged 24-59 Months in Ratahan Subdistrict, Southeast Minahasa Regency) Elshaday Kasim1)*, Nancy Malonda1), Marsella Amisi1)*Fakultas Kesehatan Masyarakat Universitas Sam Ratulangi, Manado 95115*Email korespondensi:enkasim96@gmail.comDiterima  15 Febru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0
7

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 0 publications
2
5
0
7
Order By: Relevance
“…But the results of this study are in line with research conducted by Kasim, et al (2019) who found that there was no relationship between the immunization status and the nutritional status of children aged 24-59 months according to the anthropometric index of BB/U, TB/U, and BB/TB. Immunization affects the child's infection rate and can later be related to the child's nutritional intake.…”
Section: Resultssupporting
confidence: 90%
“…But the results of this study are in line with research conducted by Kasim, et al (2019) who found that there was no relationship between the immunization status and the nutritional status of children aged 24-59 months according to the anthropometric index of BB/U, TB/U, and BB/TB. Immunization affects the child's infection rate and can later be related to the child's nutritional intake.…”
Section: Resultssupporting
confidence: 90%
“…Salah satu program yang menjadi prioritas pembangunan kesehatan tahun 2015-2019 yaitu penurunan prevalensi batita pendek yaitu dengan meningkatkan status gizi dari masyarakat. Salah satu upaya yang dilakukan dalam mengintervensi kejadian stunting pada batita yaitu dengan vaksinasi dasar yang lengkap (Kasim, Malonda & Amisi, 2019;Saputri, 2019).…”
Section: Pendahuluanunclassified
“…Salah satu program yang menjadi prioritas pembangunan kesehatan tahun 2015-2019 yaitu penurunan prevalensi balita pendek yaitu dengan meningkatkan status gizi dari masyarakat. Salah satu upaya yang dilakukan dalam mengintervensi kejadian stunting pada balita yaitu dengan vaksinasi dasar yang lengkap (Kasim, 2019).…”
Section: Pendahuluanunclassified